Development of failure evaluation method for BWR Lower head in severe accident; high temperature creep test and creep damage model - Yoshihito YAMAGUCHI (The Japan Society of Mechanical Engineers, 2017)
After the Fukushima Daiichi nuclear power plant accident due to the pacific coast of Tohoku earthquake and Tsunami, we have been developing an analysis method considering creep damage mechanisms based on three-dimensional analysis in order to estimate condition of the fuel debris and failure behavior of the reactor due to severe accidents for the early completion of the decommissioning of nuclear power plants. We have also been obtaining material properties that are not provided in existing databases or literature for the analysis. In this study, we measure the tensile and creep properties of low alloy steel, Ni-based alloy, and stainless steel at high temperatures near the melting points. Using experimental data, some parameters for the creep constitutive law and creep failure evaluation method are determined. It is confirmed that the estimated rupture time by the failure evaluation method agree well with the experimental one.